Gaps In The Implementation of Maternity Leave Policy And Its Impact on The Mental Health of Working Mothers In Indonesia - Ulfah Oktarida Sihaloho (Jurnal Ilmu Administrasi Negara, 2025)
Maternal mental health, including postpartum depression, is a growing concern in Indonesia. Despite legislative advances (e.g., Law No.4/2024 extending maternity leave), gaps remain between policy and practice. This study examines how Indonesia’s maternity leave implementation gap affects maternal mental health using public policy frameworks. A qualitative literature review was conducted of relevant Indonesian and international studies. Analysis applied Street-Level Bureaucracy theory (highlighting frontline implementers’ discretion), the Public Value perspective, and the CFIR implementation framework. We found recurring implementation barriers: limited enforcement and awareness of leave rights, employer non-compliance, and social norms discouraging leave utilization. Survey data indicate about one-third of eligible mothers did not receive the full statutory leave, and 59% did not get full wage replacement during leave. These gaps were linked to elevated stress and depressive symptoms among new mothers. International evidence suggests that more restrictive maternity leave policies are associated with higher rates of postpartum depression. From a public value standpoint, the policy’s intent to protect maternal well-being is undermined without effective execution. Findings highlight the need to strengthen enforcement, workplace accountability, and integrate maternal mental health support into maternal care. These frameworks suggest that holistic strategies (e.g., monitoring mechanisms, implementer training) are needed to bridge the implementation gap and improve outcomes for mothers.